Detection Of Extended Spectrum Β-Lactamase (ESBL) Gene Patterns Of Enterobacteriaceae In Broiler Chicken Meat Sold In Traditional Markets In The East Surabaya - Binti Mu’arofah; Radita Yuniar Arizandy; Budi Utomo; Kuntaman Kuntaman (Universitas STRADA Indonesia, 2020)
This study was to analyze the pattern of colonization of ESBL-producing bacteria and ESBL gene patterns in broiler chicken meat. Random sampling was chosen for collecting broiler chicken meat. One hundred portions of broiler chicken meat were taken from the Traditional Market in East Surabaya. This study was an observational analytic study with a cross-sectional approach. Bacteria were growth in TSB media then screened for ESBL production on McConkey Agar with Cefotaxime 2ug/ml. Afterward, continue for phenotypic screening using Double Disk Synergy Test (DDST). Finally, the detection of ESBL gene by using PCR. ESBL-producing bacteria were found in 33 (33%) broiler chicken samples with thirty positive E. coli, and three positive samples of Pseudomonas aeruginosa. Positive gene detection in SHV genes (1%), TEM genes (18%) and CTX-M genes (24%). ESBL producing bacteria have spread in broiler chicken meat (33%) sold in traditional markets, including Escherichia coli and Pseudomonas aeruginosa